Interior Convection Regime, Host Star Luminosity, and Predicted Atmospheric CO2 Abundance in Terrestrial Exoplanets - Antonin Affholder; Stéphane Mazevet; Boris Sauterey; Dániel Apai; Régis Ferrière (The Astronomical Journal)
Terrestrial planets in the habitable zone (HZ) of Sun-like stars are priority targets for detection and observation by the next generation of space telescopes. Earth's long-term habitability may have been tied to the geological carbon cycle, a process critically facilitated by plate tectonics. In the modern Earth, plate motion corresponds to a mantle convection regime called mobile lid. The alternate, stagnant-lid regime is found on Mars and Venus, which may have lacked strong enough weathering feedback to sustain surface liquid water over geological timescales if initially present. Constraining observational strategies able to infer the most common regime in terrestrial exoplanets requires quantitative predictions of the atmospheric composition of planets in either regime. We use end-member models of volcanic outgassing and crust weathering for the stagnant- and mobile-lid convection regimes, which we couple to models of atmospheric chemistry and climate and ocean chemistry to simulate the atmospheric evolution of these worlds in the HZ. In our simulations under the two alternate regimes, we find that the fraction of planets possessing climates consistent with surface liquid water is virtually the same. Despite this unexpected similarity, we predict that a mission capable of detecting atmospheric CO _2 abundance above 0.1 bar in 25 terrestrial exoplanets is extremely likely (≥95% of samples) to infer the dominant interior convection regime in that sample with strong evidence (10:1 odds). This offers guidance for the specifications of the Habitable Worlds Observatory NASA concept mission and other future missions capable of probing samples of habitable exoplanets.